Translation Of Metaphor And Simile In The Poem Asyhadu An La Imra'ata Illa Anti By Nizar Qabbani - Fitriyah, Tika; Kurniawan, Donie Fadjar; Sawardi, F.X.; Supana, Supana (Ijaz Arabi Journal of Arabic Learning, 2025)
A translation of poetry is needed to introduce the culture of the country where the poem was written. Research related to poetry translation is required to evaluate and control translated works that develop in the community. This descriptive qualitative research study examines the forms of metaphor and simile and the translation shift. The data source in this research is the poem Asyhadu an La Imraata Illa Anti and its translation translated by Musyfiqur Rahman under the title I Testify There is No Woman but You. The result of this study shows that the translator translates metaphor into metaphorical form, shifting form only found 1 case and shifting form and meaning only occurred 1 case. In simile translation, the researcher found no shift in both form and meaning aspects. This shows the translator's competence so that the form and meaning of the poem in the source language can be transferred well into the target language. It can help Arabic language and translation teachers understand the types of metaphors and how to translate them.